2012
DOI: 10.1111/j.1399-3038.2012.01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary school teachers’ knowledge about and attitudes toward anaphylaxis

Abstract: This study shows that primary school teachers are not well informed about anaphylaxis. Teachers should be given training on the subject, and there should be a re-evaluation of school and health policies with a wider global perspective. There is an urgent need to inquire into the allergy management plans and policies in schools and to develop teacher education organizations on the subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
84
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 22 publications
8
84
0
7
Order By: Relevance
“…Although deaths due to food anaphylaxis occur rarely, they may be prevented with sufficient education (21). The information level of teachers related with anaphylaxis in our country is substantially low (22). Especially families and teachers should be educated about the use of ephinephrine needle and they should be informed about what to do in emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Although deaths due to food anaphylaxis occur rarely, they may be prevented with sufficient education (21). The information level of teachers related with anaphylaxis in our country is substantially low (22). Especially families and teachers should be educated about the use of ephinephrine needle and they should be informed about what to do in emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…The reality is that many facilities are poorly prepared to protect students. Essential components of policies for the prevention of food allergen exposure are missing (1,45), teachers have poor knowledge of anaphylaxis triggers, symptoms, and AAIs (16,(46)(47)(48), and PEMPs are not currently consistently provided for the majority of students with FA (16).…”
Section: Schoolmentioning
confidence: 99%
“…Although these limitations may have limited generalizability, İstanbul is the country's largest city. Previously, Ercan et al (19) showed that elementary school teachers in Turkey are not well informed about anaphylaxis in a small sample. The Balkan Med J, Vol.…”
Section: Discussionmentioning
confidence: 99%